A vaccine for hypertension based on virus-like particles: preclinical efficacy and phase I safety and immunogenicity. - Ambühl, P; Tissot, A; Fulurija, A; Maurer, P; Nussberger, J; Sabat, R; Nief, V; Schellekens, C; Sladko, K; Roubicek, K; Pfister, T; Rettenbacher, M; et al. (2007)
BACKGROUND: Despite the availability of efficacious drugs, the success of treating hypertension is limited by patients' inconsistent drug intake. Immunization against angiotensin II may offer a valuable alternative to conventional drugs for the treatment of hypertension, because vaccines induce relatively long-lasting effects and do not require daily dosing. Here we describe the preclinical development and the phase I clinical trial testing of a virus-like particle (VLP)-based antihypertensive vaccine. METHODS AND RESULTS: An angiotensin II-derived peptide was conjugated to the VLP Qbeta (AngQb). AngQb was highly immunogenic in mice and rats. To test for efficacy, spontaneously hypertensive rats (SHR) were immunized with 400 microg AngQb or VLP alone. Group mean systolic blood pressure (SBP) was reduced by up to 21 mmHg (159 +/- 2 versus 180 +/- 5 mmHg, P < 0.001), and total angiotensin II levels (antibody-bound and free) were increased ninefold (85 +/- 20 versus 9 +/- 1 pmol/l, P = 0.002) compared with VLP controls. SHR treated with the angiotensin-converting enzyme (ACE) inhibitor ramipril (1 mg/kg per day by mouth) reached an SBP of 155 +/- 2 mmHg. Twelve healthy volunteers of a placebo-controlled randomized phase I trial were injected once with 100 microg AngQb. Angiotensin II-specific antibodies were raised in all subjects (100% responder rate) and AngQb was well tolerated. CONCLUSIONS: AngQb reduces blood pressure in SHR to levels obtained with an ACE inhibitor, and is immunogenic and well tolerated in humans. Therefore, vaccination against angiotensin II has the potential to become a useful antihypertensive treatment providing long-lasting effects and improving patient compliance.